Figs and kippers - Paul Chilton (Forum, 2019)
This article aims to connect three topics: Brexit, Boris and the decay of democracy. What connects this trio is talk, talk, talk. Language and politics are tightly and necessarily intertwined. Indeed, as the Greeks thought, language is intertwined with democracy itself. The twenty-first century has brought unprecedented complexity to human ways of communication, and yet the old rhetorical tricks and oratorical stunts, first described and practised in the ancient world, are still capable of turning heads. As we learn more about how human language works in social and political settings, we can see even more clearly a few of the factors that enable lying politicians to acquire power. But we are still far from drawing practical lessons that could be relevant to our current political crisis.